2020
DOI: 10.31234/osf.io/hfygc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Candidate evaluations across the aisle: Cross-cultural and experimental evidence that out-partisans value candidate warmth more than in-partisans

Abstract: Partisans view their own candidates through rose-colored glasses and see competing candidates much more negatively. However, recent advances in political behavior reveal that such directional motivated reasoning is not simply about love and hate but also about more nuanced shifts in preferences. Combining two insights from the psychological sciences—coalitional reasoning and a general dislike of self-interested leaders—we form the novel prediction that voters pay more attention to out-party than to in-party ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Conversely, losers of elections are more vulnerable to ill-treatment by political leadership (Bor & Laustsen, 2021). Protecting checks and balances is of crucial importance for those in opposition because their chance of winning power will decrease if the system is skewed in favor of the current rulers.…”
Section: The Role Of Political Tribalism: Partisanship and Strength Of Party Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, losers of elections are more vulnerable to ill-treatment by political leadership (Bor & Laustsen, 2021). Protecting checks and balances is of crucial importance for those in opposition because their chance of winning power will decrease if the system is skewed in favor of the current rulers.…”
Section: The Role Of Political Tribalism: Partisanship and Strength Of Party Identificationmentioning
confidence: 99%
“…Illiberal political actors can assent to power in countries with very different political systems and democratic traditions. Donald Trump in the US, Jair Bolsanaro in Brazil, Fidesz in Hungary and Law and Justice in Poland are just a few examples illustrating that majorities can elect leaders who strive to get rid of counter-majoritarian checks, restrict civic rights, and harm vulnerable minorities (Bor et al, 2021). Citizens’ response to the breaches of democratic rules is therefore critical to the survival of democracy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed negativity in the evaluation of candidates ( Bor and Lautsen, 2020 ; Christenson and Weisberg, 2019 ; Klein and Ahluwalia, 2005 ). However, only a handful of studies has explored in a systematic fashion how negative attitudes toward political leaders may affect voting behavior.…”
Section: Negative Personalizationmentioning
confidence: 99%
“…Interestingly, a few studies showed how this might affect leader evaluations in modern politics. First, concerning partisan affiliations, Bor and Laustsen (2021) showed that warmth (i.e., good intentions) constitutes a more important trait in voters' evaluations of other parties' leaders than of their own. Second, Bøggild and Laustsen (2016) found a parallel pattern across ethnic divisions.…”
Section: Future Directionsmentioning
confidence: 99%
“…The introduction of closed‐ended trait questions in the American National Election Studies (ANES) in 1980 further facilitated studies exploring the role of candidate personality in relation to the U.S. presidency (e.g., Bartels, 2002; Goren, 2002; Hayes, 2005). Consequently, the importance of candidate personality and character for political behavior across a wide range of western democracies is demonstrated (e.g., Bittner, 2011; Bor & Laustsen, 2021; Clarke, Sanders, Stewart, & Whiteley, 2004; Da Silva & Costa, 2018; Funk, 1999; Laustsen & Bor, 2017; McAllister, 2016; Ohr & Oscarsson, 2013). This section provides a nonexhaustive overview of this literature highlighting important contributions, central theories, and unanswered questions.…”
Section: Overview Of Research On Trait‐based Candidate Evaluationsmentioning
confidence: 99%